Response of ber (Ziziphus mauritiana Lamk.)cultivars against black leaf spot (Isariopsis indica var. ziziphi) disease and its correlation with weather parameters (Indian Journal of Arid Horticulture, 2013)
Ber [Ziziphus mauritiana Lamk. (Syn. Z. jujuba The experiment was carried out at Main L.)] Indian jujube also known as Narkelikul, Boroi, Bor, Experiment Station, Department of Horticulture, Narendra  Beri, Indian plum is a tropical fruit tree species belonging to Deva University of Agriculture & Technology, Kumarganj,  the family Rhamnaceae. Indian jujube is one of the two Faizabad (Uttar Pradesh) during 2008-09. Three cvs viz.,  Zizyphus species that have considerable horticultural Tikadi (with maximum resistance) cv. Gola (with importance. The other one is Chinese jujube. It is commonly moderately resistance) and Chhuhara (with minimum  found in the tropical and subtropical regions. Originally resistance) were selected for the experiment. Three plants  native to India, it is now widely naturalized in tropical for each cvs. were selected for the same. Four branches in 4  region from Africa, Afghanistan and China and in some diagonally opposite directions of each of the three plants  Pacific regions. Ziziphus spp. can be grown even on were selected and 5 healthy leaves from each of the branch  marginal land in the hot arid regions of Rajasthan. Its were selected for observations. Thus, total 60 leaves for each  cultivation has received a great impetus in recent years in the of the three groups of the cvs. were selected for the  northern part of India; especially in the states of Punjab, observations.
Keywords: Chinese jujube; Chhuhara; temperature